2013
DOI: 10.1149/2.042401jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Silicon Species in Cryolite Melt

Abstract: Electrodeposition of Si from cryolite based melts is a possible solution for mass production of solar grade silicon. The deposition potential of Si on the candidate cathode, such as graphite, is fundamental information that needs to be measured and applied to restrict the co-deposition of impurities. In this study this potential was measured using cyclic voltammetry. As the activity of SiO 2 in the electrolyte affects the deposition potential, the measurements were carried out in a range of SiO 2 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…16 and 17, it has been reported that the reduction of Si (IV) in fluoride molten salt proceeds by a two-step process. 19,[25][26][27][28] Although Si (II) compounds are usually unstable, the existence of some Si (II) compounds such as SiO and SiF 2 were reported in the cryolite-based melts. 28 In this study (NaF-AlF 3 -SiO 2 melt), Si (II) compound (SiF 2 ) is assumed to be formed by reaction 18 and 19.…”
Section: Resultsmentioning
confidence: 99%
“…16 and 17, it has been reported that the reduction of Si (IV) in fluoride molten salt proceeds by a two-step process. 19,[25][26][27][28] Although Si (II) compounds are usually unstable, the existence of some Si (II) compounds such as SiO and SiF 2 were reported in the cryolite-based melts. 28 In this study (NaF-AlF 3 -SiO 2 melt), Si (II) compound (SiF 2 ) is assumed to be formed by reaction 18 and 19.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed experimental procedure is provided in previous publications. [10,26] A typical voltammograms recorded with two different scan rates, in cryolite-5 wt pct SiO 2 at 1313 K (1040°C), is shown in Figure 2. Major cathodic and corresponding anodic peaks form due to Si deposition and re-oxidation.…”
Section: A Cyclic Voltammetry On Graphitementioning
confidence: 99%
“…The standard decomposition potential of SiO 2 has been calculated from the Nernst's equation as À1.75 V at 1313 K (1040°C). [3,10,11] In most of the researches, graphite has been used as the anode due to its resistance to the corrosive environment of molten salts. Graphite reacts with the evolved O 2 and results in the release of CO and CO 2 on the anode surface.…”
mentioning
confidence: 99%
“…Thin-film solar cells can potentially be fabricated by electrodeposition, which allows the formation of nanostructures over a large area without the use of high-voltage and high-vacuum equipment. Considering these characteristics and the very negative reduction potential of Si together with the high sensitivity of Si precursors to water, Si electrodeposition has recently been attempted in nonaqueous systems such as molten salts, [20][21][22][23][24][25] organic solvents, [26][27][28][29][30] and ionic liquids. [31][32][33] In particular, Yang et al 24) and Zou et al 25) reported the electrochemical formation of photoresponsive Si films and p-n junctions in a CaCl 2 -based molten salt mixture.…”
Section: Introductionmentioning
confidence: 99%